WRITING ABOUT THE OTHER, WE WRITE ABOUT OURSELVES (A collaboration between Aleksandar Jerkov and the Institute of Macedonian Literature in Skopje) (Philological Studies, 2025)
The subject of the paper is the cooperation of Prof. Aleksandar Jerkov from the Faculty of Philology in Belgrade with the Institute of Macedonian Literature in Skopje, which took place within the framework of the projects: "The Phenomenon of Love and its Creative Implications in the South Slavic Literatures of the 20th Century" and "Affinities between Contemporary Macedonian and Balkan Literatures (Real – Imaginary)" more than twenty-five years ago. The occasion for this retrospective is the awarding of the Golden Book Award for 2024 to my colleague Jerkov by the oldest Serbian literary, cultural and scientific institution – the Library of Matica Srpska. The paper presents in detail his three theoretical studies, published in separate collections. The first two are dedicated to the topic of love, while the third focuses on the problem of truth in the era of modernism. Through a kind of reflection, inherent to his analytical nature, he comes to several relevant conclusions, of which we emphasize: the absence of love in the literature of the 20th century; the search for it, which is reminiscent of the search for the impossible, and the paradoxical nature of modernism, which mystifies itself and translates it into a myth. The paper also explores the dilemma of the need for a new reading of the novel "That Which Was Sky" by Vlado Maleski, proposing to approach it through various discourses that are yet to be explored. The paper also presents his position on the birth of national drama, derived from the spirit of culture through a comparative analysis of the developmental beginnings of Macedonian and Serbian drama. At the end of the paper, the basic elements that comprise Jerkov's sharp critical mind are emphasized, such as the curious spirit directed towards a broader philosophical and cultural framework within which he situates the content he processes, and the complex, lengthy statements that are often interwoven with irony.
Keywords: regional cooperation, comparison, development processes, doubt, absence, search for the impossible, paradoxicality